Drama “Marry My Husband”: Narasi “Istri Membalas Dendam” sebagai Wacana Kesetaraan Gender: Penelitian - Nugraha, Agung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
In recent years, television dramas featuring the "Revenge of the Wife" narrative have become popular on streaming platforms and social media. The emergence of this narrative in the drama "Marry My Husband" signifies a new trend that has captured widespread audience interest. This qualitative study aims to analyze the narrative construction and the discourse of gender equality in "Marry My Husband" by applying Tzvetan Todorov's model of narrative theory. The findings indicate that all of Todorov's structural stages such as initial equilibrium, disruption, recognition of disruption, attempt to repair, and new equilibrium are present, with a dominant emphasis on the "attempt to repair" phase. The finding shows that "attempt to repair" phase not only forms the core of the story's tension but also functions as a medium for resisting gender stratification, depicting the female protagonist's transformation from a passive victim into a powerful agent in control of her own life. The drama's success has subsequently stimulated the creation of various similar series, indicating a significant shift in the representation of women in television and streaming media.